Molecular Diagnosis of Panel-Based Next-Generation Sequencing Approach and Clinical Symptoms in Patients With Glycogen Storage Disease: A Single Center Retrospective Study - Ying, Shen; Zhihua, Zhang; Yucan, Zheng; Yu, Jin; Qian, Lin; Bixia, Zheng; Weixia, Cheng; Zhifeng, Liu (Frontiers in Pediatrics, 2020)
Aim: The aim of this study was to investigate the clinical utility of panel-based next-generation sequencing (NGS) in the diagnostic approach of glycogen storage disease(GSD). Methods: we performed a retrospective review of the 32 cases with suspected GSDs between April 2013 and November 2019 through panel-based NGS, clinical and biochemical data and long-term complications. Results Of the 32 clinical cases, we identified 41 different variants, including 24 missense (58.5%), one synonymous (2.4%), three nonsense (8%), one splice (2.4%), four frameshift (9.8%), one deletion (2.4%), four insertions (9.8%), two deletion-insertion (4.9%) and one duplication(2.4%), of which 13(31.7%) were previously unreported in the literature. In addition, patients with different types of GSDs showed important differences in biochemical parameters (i.e., CK, rGGT, TG and UA). Conclusions The panel-based NGS played an important diagnostic role in the suspicious GSDs patients, especially in the mild phenotype and ruled out detectable pathologic conditions. Besides, differences between our GSDs patients reflect biochemical heterogeneity.